Clinicoradiological features in amyotrophic lateral sclerosis patients with olfactory dysfunction. Issue 3 (3rd April 2021) - Masuda, Michihito; Watanabe, Hirohisa; Ogura, Aya; Ohdake, Reiko; Kato, Toshiyasu; Kawabata, Kazuya; Hara, Kazuhiro; Nakamura, Ryoichi; Atsuta, Naoki; Epifanio, Bagarinao; Katsuno, Masahisa; Sobue, Gen
Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disorder characterized by motor neuron involvement. Although olfactory dysfunction has been described in ALS, clinicoradiological features associated with the olfactory dysfunction remain poorly understood. Methods : We enrolled 30 patients with ALS and age- and sex-matched 53 healthy controls (HCs). All participants underwent the odor stick identification test for Japanese (OSIT-J) and clinical assessments, including disease duration, ALSFRS-R, site of onset, forced vital capacity, and cognitive examinations that reflected the general, executive, memory and language function. We investigated the associations between OSIT-J score and clinical features and examined atrophic changes by voxel-based morphometry (VBM) analysis to MRI. Results : The OSIT-J score was significantly lower in ALS patients than HCs (6.9 ± 3.2 vs. 9.8 ± 1.9, p < 0.001). In ALS, there were significant relationships between OSIT-J score and age at examination, frontal assessment battery, word fluencies, digit span forward, and ADAS-Jcog recognition, but not education, disease type, duration, ALSFRS-R and, %VC. Multiple regression analysis with stepwise method showed the only ADAS-Jcog recognition substantially predicted OSIT-J score. VBM analysis with age, sex, total intracranial volume, and ADAS-Jcog recognition as covariates showed OSIT-J scores were substantially correlated with atrophic changes of left orbital cortex consisting of gyrus rectus and medial orbital gyrus and right hippocampus in ALS. Conclusion : ALS patients could show substantial olfactory dysfunction in association with orbital cortex and hippocampus involvements. The olfactory examination could be a useful marker for screening of frontotemporal alteration in ALS.